The vital role of women in science: analysis of Hidden Figures (2016) - Serrano Martín, Carlos (Comunicación y Género [Communication and Gender], 2023)
This work is based on the premise that the influence of women scientists in the great advances of human knowledge should not be ignored. For this reason, we analyze the content, under a qualitative approach, of the footage of Hidden Figures (Hidden Figures, Theodore Melfi, 2016). It gives the protagonism to a group of female engineers and mathematicians without whose collaboration, perhaps, the race for the conquest of space in the United States would have been very different.
Keywords: Cinema; Science; Space Race; Cold War; Women Scients; Feminism